Answer:
The rigth answer is, x = 1
Step-by-step explanation:
As:
f (x) = 3/4 x + 12
They separate the terms:
3/4 x = 12
Then, what you are multiplying happens to divide:
x = 12/1/3/4
Media are divided by means and ends with ends, and we have as a result that:
x = 3/3 = 1
Answer:
The answer I got from the equation was 254.47
Answer:
Doesn't make sense. Please re-punctuate your question.
Step-by-step explanation:
Do you have a picture of the question??
Answer:
-1
Step-by-step explanation:
We can plug in -3 for x and solve:
f(-3) = -3 + 2
= -1